Commemorating a Providential Conquest in Valencia: The 9 October Feast - Granell Sales, Francesc (Religions, 2022)
From 1338 onwards, the inhabitants of late-medieval Valencia celebrated a feast every 9 October commemorating the entrance into the city of King James I’s forces on that day in 1238. It has been argued that this was essentially a spiritual display from its establishment in 1338 until the beginning of the fifteenth century. The present study delves deeper into the religious and political aims of the feast from its origins, framing the celebration within a broader Mediterranean context. The first part analyses the 9 October feast in relation to two medieval liturgies that also commemorated crusading victories against Islam: the "Feast of the Liberation of Jerusalem" and the "Feast of the Banner of Majorca". The second part focuses on the combination of performance and images during the ceremony, leading to the conclusion that the 9 October procession had similar goals to those in Jerusalem and Majorca. Indeed, the ceremony intended to convey an interpretation of the conquest as the continuation of Biblical history because it visibly and orally aligned the capture of Valencia with divine will and the sacred Scriptures.